MRGPRX2 signaling involves the Lysyl-tRNA synthetase and MITF pathway - Guo, Yanru; Ollé, Laia; Proaño-Pérez, Elizabeth; Aparicio, Cristina; Guerrero, Mario; Muñoz-Cano, Rosa; Martín, Margarita (Frontiers in Immunology, 2023)
MRGPRX2, a G-protein-coupled-seven transmembrane domain receptor, is mainly expressed in mast cells and neurons and is involved in skin immunity and pain. It is implicated in the pathophysiology of non-IgE-mediated immediate hypersensitivity and has been related to adverse drug reactions. Moreover, a role has been proposed in asthma, atopic dermatitis, contact dermatitis, and chronic spontaneous urticaria. Although it has a prominent role in disease, its signaling transduction is poorly understood. This study shows that MRGPRX2 activation with substance P increased Lysyl t-RNA synthetase (LysRS) translocation to the nucleus. LysRS is a moonlighting protein with a dual role in protein translation and IgE signaling in mast cells. Upon allergen- IgE-FcεRI crosslinking, LysRS is translocated to the nucleus and activates microphthalmia-associated transcription factor (MITF) activity. In this study, we found that MRGPRX2 triggering led to MITF phosphorylation and increased MITF activity. Therefore, overexpression of LysRS increased MITF activity after MRGPRX2 activation. MITF silencing reduced MRGPRX2-dependent calcium influx and mast cell degranulation. Furthermore, a MITF pathway inhibitor, ML329, impaired MITF expression, calcium influx, and mast cell degranulation. Moreover, drugs such as atracurium, vancomycin, and morphine, reported to induce MRGPRX2-dependent degranulation, increased MITF activity. Altogether, our data show that MRGPRX2 signaling enhances MITF activity, and its abrogation by silencing or inhibition resulted in defective MRGPRX2 degranulation. We conclude that MRGPRX2 signaling involves the LysRS and MITF pathway. Thus, MITF and MITF-dependent targets may be considered therapeutic approaches to treat pathologies where MRGPRX2 is implicated.